Identity, stigma, and HIV risk among transgender women: a qualitative study in Jiangsu Province, China - Zi-Han Yan; Jessica Lin; Wen-Jing Xiao; Keh-Ming Lin; Willi McFarland; Hong-Jing Yan; Erin Wilson (BMC, 2019)
Abstract Background Transgender women have multiple disparities globally, including social rejection and stigma, HIV infection and untreated mental health problems. However, few data on transgender women are available in China. Therefore, this study aimed to explore transgender women's experiences on gender identity, disclosure, discrimination, transgender-specific medical care, and perceptions of HIV and sexually transmitted infections (STI) risk in China. Methods A qualitative study was conducted in Nanjing and Suzhou city, China in 2018. Key informant interviews (n = 14) and focus group discussions (n = 2) with diverse transgender women were implemented. Text was transcribed and translated, and Dedoose™ software was used for coding, analysis and interpretation by the research team. Results Chinese transgender women share experiences with transgender women worldwide, including a long and challenging identity search, stigma and discrimination, poor access to trans-specific services and unmet needs for mental health care. Features unique to them include terms used for self-identification, culturally-shaped expectations for reproduction, and ideals of placing the familial and societal welfare over personal fulfillment. Social networks of this population appear sparse, scattered, and underground. Familial rejection was experienced by nearly all respondents. Perceptions of HIV and STI risk and history of HIV testing were notably low. Conclusions Transgender women in China face high social rejection and discrimination along with unmet need for various types of healthcare. Scaling up transgender-specific services including gender-affirming medical care, mental health care and HIV/STI prevention are warranted to address the social, medical and mental health of transgender women in China.